PEWARISAN DZAWIL ARHAM BERSAMA ASHABUL FURUDH (Analisis Terhadap Putusan Pengadilan Tinggi Agama Bangka Belitung No. 4/Pdt.G/2020/PTA.BB) - Khusnul Khotimah (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2022)
This research was motivated by the decision of the Bangka Belitung Religious High Court No.4/Pdt.G/2020/PTA.BB decided on the inheritance case, which in the decision decided that the heirs of dzawil arham got a share of the inheritance when he was with the heirs of dzawil furudh. Whereas the provisions of dzawil arham get the inheritance from the heir when the heirs of ashabul furud and ashabah are not present. This thesis is the result of a research entitled